Improvement of the Mouse Grimace Scale set-up for implementing a semi-automated Mouse Grimace Scale scoring (Part 1) - Ernst, Lisa; Kopaczka, Marcin; Schulz, Mareike; Talbot, Steven R.; Zieglowski, L.; Meyer, M.; Bruch, Stefan; Merhof, Dorit; Tolba, Rene H. (Laboratory Animals, 2020)
The Mouse Grimace Scale (MGS) has been widely used for the noninvasive examination of distress/pain in mice. The aim of this study was to further improve its performance to generate repeatable, faster, blinded and reliable results for developing automated and standardized pictures for MGS scoring and simultaneous evaluation of up to four animals. Videos of seven C57BL/6N mice were generated in an experiment to assess pain and stress induced by repeated intraperitoneal injection of carbon tetrachloride (CCl4). MGS scores were taken 1 h before and after the injection. Videotaping was performed for 10 min in special observation boxes. For manual selection, pictures of each mouse were randomly chosen for quality analysis and scored according six quality selection criteria (0 = no, 1 = moderate, 2 = full accordance); the maximum possible score was 12. Overall, 609 pictures from six videos were evaluated for MGS scoring quality; evaluation was performed by using the picture selection tool or by manual scoring. With manual scoring, 288 pictures (48.3% of all randomly generated pictures) were deemed scorable using MGS (mean score = 22.15 ± SD 6.3). To evaluate the algorithm, ratings from different rater groups (beginner, medium-level trained, professional) were compared with the automated image generated. These differences were not significant (p = 0.1091). This study demonstrates an improved set-up and a picture selection tool that can generate repeatable, not-observer biased and standardized pictures for MGS scoring.
CRIS-Team Scopus Importer:2023-03-23
Keywords: behaviour; distress; ethics and welfare; MGS; pain measurement; severity